2000
DOI: 10.1530/eje.0.1420402
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin with C-elongated alpha-subunit retains full receptor binding and partial agonist activity

Abstract: Objective: To test whether extension of the C-terminus of human chorionic gonadotropin (hCG) a-subunit (ha) alters the bioactivity of the recombined ab heterodimer. Design: The stop codon of ha was mutated to produce a 24 amino acid extension. Methods:The extended ha (a +24 ) was co-expressed with hCGb in COS-7 cells and the receptor binding and in vivo bioactivity of the secreted hormone was compared with its wild-type counterpart.Results: This extension did not impair the binding of hCG to rat LH/CG receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…We first focused on this C-terminal part of the a-subunit as deletion and mutagenesis studies had previously shown that this region in the human a-subunit was important for binding and bioactivity of gonadotropins (11-13, 29 -31). Moreover, hCG with its a-subunit elongated by 24 residues beyond the terminal serine displayed full receptor binding and a sixfold reduction in LH bioactivity assessed on rat Leydig cells (32). However, this study shows that the mutations introduced in the C-terminal part of a-dk did not abolish FSH activity of dkLH or eLH, showing that these unique positions in the equid a-subunits do not favor interaction with the FSH receptor.…”
Section: Discussionmentioning
confidence: 61%
“…We first focused on this C-terminal part of the a-subunit as deletion and mutagenesis studies had previously shown that this region in the human a-subunit was important for binding and bioactivity of gonadotropins (11-13, 29 -31). Moreover, hCG with its a-subunit elongated by 24 residues beyond the terminal serine displayed full receptor binding and a sixfold reduction in LH bioactivity assessed on rat Leydig cells (32). However, this study shows that the mutations introduced in the C-terminal part of a-dk did not abolish FSH activity of dkLH or eLH, showing that these unique positions in the equid a-subunits do not favor interaction with the FSH receptor.…”
Section: Discussionmentioning
confidence: 61%
“…Fusion of peptides to this portion of the ␣-subunit has been shown to have varying effects on hormone activity (20,21). Therefore, when we began these studies we were concerned that the presence of a crosslink between the ␣CT and the hCG ␤-subunit might destroy heterodimer activity by a mechanism that was unrelated to the ability of this portion of the hormone to contact the LHR.…”
Section: Resultsmentioning
confidence: 99%
“…The activities of analogs in which the seatbelt is latched to residues at or near the carboxyl terminus, albeit low, offer additional insights into the role of this hormone region in receptor interactions. The very end of the ␣-subunit carboxyl terminus appears to be exposed in the lutropin receptor complex as shown by the finding that a few residues can be added to this site without disrupting hormone activity (37). This portion of the hormone may be near the receptor interface, however, as shown by the finding that the presence of hCG ␤-subunit residues 118 -145, a region that contains several glycosylated serine residues in hCG, reduced the activity of hCG ϳ50-fold (38).…”
Section: Figmentioning
confidence: 99%